2020
DOI: 10.1002/adsc.201901360
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Dependent Enantiodivergent Friedel‐Crafts Reaction of Arylsulfonyl Indoles with 1‐Naphthols

Abstract: We reported a solvent‐controlled enantiodivergent Friedel‐Crafts reaction of 1‐naphthols with vinylogous imine intermediates, which were generated from arylsulfonyl indoles. This reaction was catalyzed by a single cinchona alkaloid bifunctional organocatalyst and could produce both enantiomers by using toluene or 1,2‐DCE as the solvents. Eyring plot analysis revealed that enthalpy‐entropy compensation dominates this enantiodivergent reaction. DFT calculation was used to probe and compare the R‐ and S‐selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…On the basis of the X-ray crystal structure results, previous studies 14,15 and control experiments, the plausible reaction mechanisms for the o - and p -selective Friedel–Crafts reactions were proposed. As shown in Scheme 4a, the o -selective Friedel–Crafts reaction is initiated by the base-triggered deprotonation of 1-naphthol 2a by quinuclidine amine of the catalyst to give the anionic intermediate o -A-IM1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the X-ray crystal structure results, previous studies 14,15 and control experiments, the plausible reaction mechanisms for the o - and p -selective Friedel–Crafts reactions were proposed. As shown in Scheme 4a, the o -selective Friedel–Crafts reaction is initiated by the base-triggered deprotonation of 1-naphthol 2a by quinuclidine amine of the catalyst to give the anionic intermediate o -A-IM1 .…”
Section: Resultsmentioning
confidence: 99%
“…14 b To the best of our knowledge, this is the first example of an organocatalytic regiodivergent enantioselective Friedel–Crafts reaction of 1-naphthols. Inspired by this work and our continuous efforts to develop organocatalytic asymmetric Friedel–Crafts reactions, 15 we herein report a successful organocatalyst-controlled site-selectivity switchable Friedel–Crafts reaction of 1-naphthols with 2,3-dioxopyrrolidines, affording polycyclic pyrrolidinone derivatives in good to high reaction yields (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chang 52 et al disclosed a solvent dependent enantiodivergent synthesis of both enantiomers of 69 by the Friedel–Crafts reaction of 1-naphthols 68 with arenesulfonyl indoles (25) using a single quinine derived bifunctional organocatalyst VIII ( Scheme 22 ). The resultant ( S )-69 was obtained using toluene as the solvent in 71–99% yields and up to 99% ee, while the ( R )-enantiomer was obtained using 1,2-dichloroethane in 67–99% yields and up to 99% ee.…”
Section: Reactions Of Arenesulfonyl Indolesmentioning
confidence: 99%
“…Spirooxindole dihydropyranones are a key structural element in a number of natural products and synthetic bioactive molecules . As a part of our continuing efforts to develop organocatalytic asymmetric reactions for enantioenriched spirooxindole dihydropyranones, we herein report the successful reversal of enantioselectivity in a vinylogous aldol–cyclization cascade reaction catalyzed by bifunctional tertiary amines, simply by changing the hydrogen-bond donor of the catalyst from thiourea to squaramide (Scheme ). In this study, we observed that it is possible to control the enantioselectivity simply by changing the structure of H-bond donors based on the above mechanistic insights.…”
Section: Introductionmentioning
confidence: 99%